2012
DOI: 10.1111/eva.12022
|View full text |Cite
|
Sign up to set email alerts
|

Stocking impacts the expression of candidate genes and physiological condition in introgressed brook charr (Salvelinus fontinalis) populations

Abstract: Translocation of plants and animal populations between environments is one of the major forms of anthropogenic perturbation experienced by pristine populations, and consequently, human-mediated hybridization by stocking practices between wild and exogenous conspecifics is of increasing concern. In this study, we compared the expression of seven candidate genes involved in multifactorial traits and regulatory pathways for growth as a function of level of introgressive hybridization between wild and domestic bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 87 publications
3
37
0
Order By: Relevance
“…; Lamaze et al . ). Therefore, although potential benefits of genetic rescue should not be neglected in such contexts, we suggest that caution should be taken to avoid alteration of local adaptation, in particular adaptation related to the trophic niches.…”
Section: Discussionmentioning
confidence: 97%
“…; Lamaze et al . ). Therefore, although potential benefits of genetic rescue should not be neglected in such contexts, we suggest that caution should be taken to avoid alteration of local adaptation, in particular adaptation related to the trophic niches.…”
Section: Discussionmentioning
confidence: 97%
“…; Lamaze et al. , ). Even though the extent of local adaptations in lake trout remains largely unknown, stocking could alter local adaptation in wild populations, as shown in other fish species (reviewed in Laikre et al.…”
Section: Discussionmentioning
confidence: 97%
“…Whether admixed populations would present an advantage cannot be answered at this stage. However, recent studies on brook charr have shown that selection may favor increased introgression between stocked domestic fish and wild populations at genes involved in important phenotypic traits such as growth and that such introgression also affect levels of gene expression and physiological status, namely condition factor (Lamaze et al 2012a, 2012b). Certainly, further work is needed to highlight how different wild populations could cope with the anticipated climate modifications and how wildlife management practices of wild populations will adjust to these new challenges.…”
Section: Discussionmentioning
confidence: 99%